Emergency department’s resource utilization by the neonates: experience from emergency department at a tertiary care hospital of a LMIC - Wasif Ilyas Vohra; Muhammad Nasheet Sagri; Ahmed Raheem; Rida Jawed; Jawad Fazal; Surraiya Bano (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate neonatal presentation patterns in an emergency care setting. Method: The retrospective chart review was conducted at the Emergency Department of Aga Khan University Hospital, Karachi, in February 2021, and comprised data of neonates presenting from January to December 2019. Data was analysed using SPSS 21. Results: There were 1,403 paediatric patients with median age at presentation 6 days (interquartile range: 3-11 days) and median weight 2.8kg (interquartile range: 2.4-3.17kg). The major complaint at presentation was yellow discolouration of skin in 659(47%) patients. Neonatal jaundice was the most common diagnosis 660(47%), followed by sepsis 338(24%). The length of stay was <4 hours for 631(45 %) of the neonates. A total of 1,138(81%) patients required intravenous cannulation, 650(46%) were managed with phototherapy and 91(7%) were ventilated. In terms of outcomes, 722(52%) neonates were admitted to step-down unit, and 314(22%) to neonatal intensive care unit, while 27(2%) died. Conclusion: Neonatal jaundice was found to be the most common diagnosis in neonates presenting to the emergency department of a tertiary care hospital. Key Words: Neonates, Newborn, Health resource, Emergency treatment.